Isolation and Characterization of Mms-Sensitive Mutants of SACCHAROMYCES CEREVISIAE - Prakash, Louise (1977)
We have isolated mutants sensitive to methyl methanesulfonate (MMS) in Saccharomyces cerevisiae. Alleles of rad1, rad4, rad6, rad52, rad55 and rad57 were found among these mms mutants. Twenty-nine of the mms mutants which complement the existing radiation-sensitive (rad and rev ) mutants belong to 22 new complementation groups. Mutants from five complementation groups are sensitive only to MMS. Mutants of 11 complementation groups are sensitive to UV or X rays in addition to MMS, mutants of six complementation groups are sensitive to all three agents. The cross-sensitivities of these mms mutants to UV and X rays are discussed in terms of their possible involvement in DNA repair. Sporulation is reduced or absent in homozygous diploids of mms mutants from nine complementation groups.